Informed consent in randomised controlled trials: further development and evaluation of the participatory and informed consent (PIC) measure - Wade, J; Humphrys, E; Realpe, AX; Gaunt, DM; Burt, J (BioMed Central, 2023)
Background: Informed consent is an accepted ethical and legal prerequisite for trial participation, yet there is no standardised method of assessing patient understanding for informed consent. The participatory and informed consent (PIC) measure was developed for application to recruitment discussions to evaluate recruiter information provision and evidence of patient understanding. Preliminary evaluation of the PIC indicated the need to improve inter-rater and intra-rater reliability ratings and conduct further psychometric evaluation. This paper describes the assessment, revision and evaluation of the PIC within the context of OPTiMISE, a pragmatic primary care-based trial. Methods: This study used multiple methods across two phases. In phase one, one researcher applied the existing PIC measure to 18 audio-recorded recruitment discussions from the OPTiMISE study and made detailed observational notes about any uncertainties in application. Appointments were sampled to be maximally diverse for patient gender, study centre, recruiter and before and after an intervention to optimise information provision. Application uncertainties were reviewed by the study team, revisions made and a coding manual developed and agreed. In phase two, the coding manual was used to develop tailored guidelines for applying the PIC to appointments within the OPTiMISE trial. Two researchers then assessed 27 further appointments, purposively sampled as above, to evaluate inter-rater and intra-rater reliability, content validity and feasibility. Results: Application of the PIC to 18 audio-recorded OPTiMISE recruitment discussions resulted in harmonisation of the scales rating recruiter information provision and evidence of patient understanding, minor amendments to clarify wording and the development of detailed generic coding guidelines for applying the measure within any trial. Application of the revised measure using these guidelines to 27 further recruitment discussions showed good feasibility (time to complete), content validity (completion rate) and reliability (inter- and intra-rater) of the measure. Conclusion: The PIC provides a means to evaluate the content of information provided by recruiters, patient participation in recruitment discussions and, to some extent, evidence of patient understanding. Future work will use the measure to evaluate recruiter information provision and evidence of patient understanding both across and within trials.